Recruitment rates, retention rates, and follow-up completion in a Brief Intervention and Contact trial for suicidal behavior: a feasibility study - Divya Soni; Balpreet Panesar; Alexander Dufort; Lucy Guan; Jennifer Lee; Dana Waldern; Stephanie Hathaway; Nitika Sanger; Sid Stacey; Luciano Minuzzi; Lehana Thabane; Zainab Samaan (Pilot and Feasibility Studies)
Abstract Background Suicide is a serious public health concern for which there are limited evidence-based interventions being employed. This feasibility study administered a Brief Intervention and Contact (BIC) trial adopted from the WHO Multisite Intervention Study on Suicidal Behaviors (SUPRE-MISS) and followed participants after they had been discharged from the inpatient hospital setting. Aims To assess the recruitment and retention rates, follow-up visit completion, barriers to recruitment and retention, resources needed of employing this study, and data completion. Methods Eligible participants were recruited from psychiatric inpatient settings, in Hamilton, Ontario. Adults with suicidal behavior were randomly allocated to BIC (intervention) plus treatment as usual (TAU) or treatment as usual (control) and were followed for 6 months. The intervention arm completed 9 follow-up points during the 6-month follow-up period post-discharge. Calculation of recruitment and retention rates and associated statistical analyses were completed using SPSS version 25. Results A total of 154 participants were approached during the 8-month recruitment period, 60 participants were enrolled resulting in a recruitment rate of 7.625 participants per month. A total of 61 participants were recruited, with 1 duplicate. The retention rate was 47.5% for the recruited participants at the end of the study. Conclusions Few suicide-based follow up interventions assess the feasibility of conducting the study. Retention was low for this study; however, participants outlined reasons for withdrawal that are consistent with other research areas related to mental health. Findings from this study will help inform suicide research on the barriers and challenges to participant recruitment and retention. Trial registration NCT03825354, Registered January 30 th, 2019, ClinicalTrial.gov; https://clinicaltrials.gov/study/NCT03825354?cond=suicide&term=brief%20intervention%20and%20contact&rank=6